1995
DOI: 10.1095/biolreprod52.5.997
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Steroidogenesis in the Cebus Monkey throughout Postnatal Development1

Abstract: There is scant information on testicular steroidogenesis during postnatal development in monkeys, particularly in New World species. Our purpose was to study the in vitro steroidogenic capacity of the Cebus monkey testis from birth to advanced puberty. Fresh testicular tissue was incubated in Medium 199 with or without hCG (10 IU/ml); and levels of pregnenolone (P5), dehydroepiandrosterone (DHA), progesterone (P4), androstenedione (A), testosterone (T), dihydrotestosterone (DHT), and 3 alpha-androstanediol (3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Serum concentrations of 17-OHP and testosterone were measured by commercial RIA kits (Diagnostics Products Corporation, Los Angeles, CA, USA and ICN Pharmaceuticals, Costa Mesa, CA, USA). Androstenedione was measured by RIA after ether extraction, as previously described by Rey et al (22). RIA of estradiol-17b and estrone was carried out using commercial kits (Diagnostics Products Corporation and Diagnostic Systems Laboratories Inc., Webster, TX, USA).…”
Section: Assaysmentioning
confidence: 99%
“…Serum concentrations of 17-OHP and testosterone were measured by commercial RIA kits (Diagnostics Products Corporation, Los Angeles, CA, USA and ICN Pharmaceuticals, Costa Mesa, CA, USA). Androstenedione was measured by RIA after ether extraction, as previously described by Rey et al (22). RIA of estradiol-17b and estrone was carried out using commercial kits (Diagnostics Products Corporation and Diagnostic Systems Laboratories Inc., Webster, TX, USA).…”
Section: Assaysmentioning
confidence: 99%
“…Additionally, theory concerning dominance cues in humans suggests a link between dominant behaviour and testosterone (e.g. [22]), with a pubertal spike in testosterone and consequent changes in morphology and behaviour [23], [24]. Such developmental changes may also occur for human fWHR given its association with adult levels of testosterone [25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ginther et al (2002) found that the onset of puberty in cotton-top tamarins was marked by a significant rise in urinary DHT:T and remained elevated thereafter. In brown capuchin monkeys ( Sapajus [ Cebus ] apella ), metabolism of T into DHT in vitro testicular cells increased at the onset of puberty and continued into adulthood, though overall DHT levels were relatively low in comparison to other androgens (Rey et al, 1995). DHT production in maturing testicular cells and a subsequent increase in sexually mature individuals appears to be common among anthropoids and has been shown via in vitro analysis of testicular tissue in olive baboons ( Papio anubis ), rhesus macaques ( Macaca mulatta ), and orangutans ( Pongo pygmaeus ) (Preslock, 1980).…”
Section: Introductionmentioning
confidence: 99%